Conventions under Heterogeneous Behavioural Rules - Newton, Jonathan (Review of Economic Studies, 2021)
Abstract Strategies of players in a population are updated according to the behavioural rules of agents, where each agent is a player or a coalition of players. It is known that classic results on the stochastic stability of conventions are due to an asymmetry property of the strategy updating process. We show that asymmetry can be defined at the level of the behavioural rule and that asymmetric rules can be mixed and matched whilst retaining asymmetry of the aggregate process. Specifically, we show robustness of asymmetry to heterogeneity within an agent (Alice follows different rules at different times); heterogeneity between agents (Alice and Bob follow different rules); and heterogeneity in the timing of strategy updating. These results greatly expand and convexify the domain of behavioural rules for which results on the stochastic stability of conventions are known.